Sexual Violence Prevention Education through Snakes and Ladders Game for Adolescents at Thamavitya Mulniti School Thailand - Rapotan Hasibuan; Siti Kholijah; Putra Apriadi Siregar; Nuraisyah Wulandari Panjaitan; Arfan Mapa (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Child sexual abuse is increasingly common in many countries and is a global concern. The Multi-disciplinary Teams (MDTs) reported 2,250 children recorded cases involving other forms of sexual violence such as molestation with a range of 561 boys and 1,689 girls. Child sexual abuse is still frequent and unresolved in Thailand. Sex education is essential for health promotion, and media plays an important role in promoting individual health status and prevention efforts. This study aims to educate the prevention of sexual violence through educational game media, namely snakes and ladders for adolescents to see the level of knowledge of adolescents regarding the prevention of sexual violence. This study is a quantitative study using a one group pretest posttest design, namely by conducting a pretest and posttest on 31 students at Thamavitya Mulniti School Thailand. Data on pre-test scores and post-test scores were analyzed using Paired Samples T-test with a 95% confidence level. Students' knowledge was obtained before education and snake and ladder games with an average score of 74.97 and students' knowledge after education and snake and ladder games with an average score of 83.16. The results of the study obtained P-Value 0.006≤0.05 means that at Alpha 5% there is a difference between the average knowledge of Pre-Test and Post-Test. There was an increase in student knowledge between before the intervention and after the intervention. The conclusion of this study is that there is an effect of sexual violence education with snakes and ladders on increasing adolescent knowledge.Keywords: Adolescent, sexual violence, snakes and ladders game